Improving school management in low and middle income countries: A systematic review - Gautam Anand; Aishwarya Atluri; Lee Crawfurd; Todd Pugatch; Ketki Sheth (Global Labor Organization (GLO), 2023)
Improving school quality in low and middle income countries (LMICs) is a global priority. One way to improve quality may be to improve the management skills of school leaders. In this systematic review, we analyze the impact of interventions targeting school leaders' management practices on student learning. We begin by describing the characteristics and responsibilities of school leaders using data from large, multi-country surveys. Second, we review the literature and conduct a metaanalysis of the causal effect of school management interventions on student learning, using 39 estimates from 20 evaluations. We estimate a statistically significant improvement in student learning of 0.04 standard deviations. We show that effect sizes are not related to program scale or intensity. We complement the meta-analysis by identifying common limitations to program effectiveness through a qualitative assessment of the studies included in our review. We find three main factors which mitigate program effectiveness: 1) low take-up; 2) lack of incentives or structure for implementation of recommendations; and 3) the lengthy causal chain linking management practices to student learning. Finally, to assess external validity of our review, we survey practitioners to compare characteristics between evaluated and commonly implemented programs. Our findings suggest that future work should focus on generating evidence on the marginal effect of common design elements in these interventions, including factors that promote school leader engagement and accountability.
Keywords: 330